DEVELOPMENT OF LEADERSHIP TEACHING MATERIALS BASED ON THE ELABORATION MODEL OF EDUCATION AND TRAINING BOARD GORONTALO PROVINCE (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The objectives of this study were to 1) To design teaching materials for training courses to build an effective team based on the elaboration model starting from making the epitome, elaborating gradually, synthesizing, to making a summary and 2) To test the effectiveness of teaching material products developed in increasing participant competence training. This study uses the Research and Development method. The data collection technique is to carry out observations made on education and training participants, the head of echelon III and using a questionnaire.